Gene therapy approaches to restore ciliary function in CRISPR-Cas9 zebrafish mutant models of Primary Ciliary Dyskinesia - Rasteiro, Margarida (2024)
Cilia are involved in several processes in the body. The most relevant process for this work are the left-right axis establishment and the mucociliary clearance, the self-cleaning mechanism of the lungs. This study delves into pivotal aspects of Primary Ciliary Dyskinesia (PCD) treatment development, with a primary focus on assessing mRNA-based protein replacement's efficacy in restoring motility to olfactory (OP) cilia in zebrafish ccdc40 mutants. Notably, CCDC40 mutations are associated with a poorer prognosis, underscoring their clinical significance. The initial phase of this work involved characterizing the ccdc40 mutant, shedding light on distinct ciliary dysfunction mechanisms, prompting further inquiry. In the subsequent phase, we successfully restored cilia motility through mRNA therapy, highlighting its potential in addressing PCD's structural and functional abnormalities. This research, along with related studies, represents the dawn of personalized medicine for the diverse PCD genetic landscape, starting with mutation identification as a pivotal step. We underline the importance of mutation identification through a patient case, emphasizing the need for continued research to uncover potential links between specific gene mutations and the requirement of a lung transplant. Furthermore, identifying the patient mutation can unlock access to emerging therapies that start to be available through clinical trials, potentially delaying or preventing the need for lung transplants and their associated long-term complications. Additionally, we discuss the discrepancy in cilia beating frequency (CBF) as an indicator of ultrastructural defects, underscoring the complexity of PCD. The contrasting cilia phenotypes in monociliated and multiciliated cells carrying the same mutation suggest distinct regulatory pathways. In conclusion, our findings hold promise for mRNA-based therapies in addressing PCD, particularly in CCDC40 mutations, potentially transforming disease management and enhancing patients' quality of life.